1999
DOI: 10.1093/ajhp/56.10.985
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility and stability of vincristine sulfate, doxorubicin hydrochloride, and etoposide in 0.9% sodium chloride injection

Abstract: dministering cancer chemotherapy by continuous intravenous infusion (CIVI) has several potential advantages over administration by short intravenous infusions 1 and has been facilitated by the development of portable infusion pumps. 2 In a study by Wilson et al., 3 the EPOCH regimen-etoposide, prednisone, vincristine, cylophosphamide, and doxorubicin-was shown to be highly effective and well tolerated in patients with relapsed or refractory non-A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Several studies of vincristine solutions have been performed. Most of the studies reported that vincristine solutions are stable for several days at 25 • C or less, are not sensitive to light, and store well in plastic containers [18][19][20][21][22]. It has also been reported that the storage and handling conditions of plasma samples containing vincristine is critical to the outcome of the analysis [23].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies of vincristine solutions have been performed. Most of the studies reported that vincristine solutions are stable for several days at 25 • C or less, are not sensitive to light, and store well in plastic containers [18][19][20][21][22]. It has also been reported that the storage and handling conditions of plasma samples containing vincristine is critical to the outcome of the analysis [23].…”
Section: Resultsmentioning
confidence: 99%
“…As a result regarding the possibility of infusing in outpatient setting, there are many articles about stability and compatibility of etoposide-vincristinedoxorubucin (EPOCH-regimen) mixed together and infused over 96 h continuously for the treatment of lymphoma. 2 Wolfe et al 7 demonstrated that, in admixture containing all three drugs in concentration simulating clinical use, the drugs were stable for 72 h at 23-25 C, provided that the concentration of etoposide was less the 250 lg/mL. Indeed, at high concentration, etoposide precipitates from formulation quickly, causing concerns about drug delivery and safety.…”
Section: Chemical and Physical Stability Datamentioning
confidence: 99%
“…Differently from other chemotherapy regimens (e.g. EPOCH or IFO þ Mesna) for which data stability have been the subject of further investigations, 1,[7][8][9][10][11][12] in these specific cases data stability and data compatibility with different materials and/or infusion devices are provided into the Summary of product characteristics (SPC). 13,14 This makes the choice about the way and the time of infusion easier: in the usual approach to drug administration in outpatient setting, a number of infusionpump reservoirs could be filled, dispensed to the patient and refrigerated until use; alternatively and preferably a portable infusion pump designed to administer the total dosage over several days is used (a single container is filled and dispensed to the patient for short-term storage and prolonged use).…”
Section: Introductionmentioning
confidence: 99%
“…The compatibility and stability of the vincristine sulphate, doxorubicin hydrochloride and etoposide for the treatment of relapsed or refractory non‐Hodgkin's lymphoma has been investigated before . In this study, we used the less toxic epirubicin hydrochloride and the more accessible vindesine sulphate, and the compatibility and stability of etoposide, epirubicin hydrochloride and vindesine sulphate in one non‐PVC infusion bag under clinical conditions was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs are compatible and thus are often combined. These admixtures also appear to be stable for up to 72 hours in 0.9% sodium chloride (NaCl) . Despite the good therapeutic effectiveness of these admixtures, the toxicity of vincristine sulphate and doxorubicin hydrochloride cannot be ignored …”
Section: What Is Known and Objectivesmentioning
confidence: 99%